Ionizing radiation increases primary cilia incidence and induces multiciliation in C2C12 myoblasts - Filipová, Alžběta; Diaz-Garcia, Daniel; Bezrouk, Aleš; Čížková, Dana; Havelek, Radim; Vávrová, Jiřina; Dayanithi, Govindan; Řezacová, Martina (Cell biology international, 2015)
Primary cilia act as physical-chemical sensors and their functions include the perception of the extracellular milieu, regulation of organogenesis, and cell polarity. In general, these cells are monociliated and the single cilium possesses diverse receptors and channels which are involved in morphogenesis and growth signaling, and are, therefore, important for cell proliferation and differentiation. In this study, we used an in vitro model of C2C12 myoblasts to evaluate the effect of DNA damage induced by gamma ionizing radiation on primary cilia incidence. A significantly higher number of ciliated cells were observed after 1 day post-irradiation with 2-20 Gy when compared with non-irradiated cells. After 3 days post-irradiation, the cilia incidence in cells had decreased slightly when treated with 2, 6, and 10 Gy, although an increase in incidence rate was observed in cells treated with 20 Gy. Multi-ciliated cells were also detected in myoblasts irradiated with 10 and 20 Gy but not in non-irradiated cells or after low irradiation (2-6 Gy). Irradiation also caused a dose-dependent decrease in cell viability and proliferation and corresponding cell cycle arrest. Furthermore, an activation of caspases 3/7, 8, and 9 was observed after higher radiation (10 and 20 Gy) with increased apoptosis. Together, our results show that irradiation by gamma rays promotes myoblast ciliogenesis, with pronounced effects observed after 3 days post-irradiation. We conclude that irradiation doses of 10 and 20 Gy are sufficient to induce cell death and are responsible for the formation of multiple cilia originating from multiple basal bodies.
Keywords: buněčná diferenciace; multiple cilia; Myoblasts; cilie; Centrosome; Humans; vztah dávky záření a odpovědi; DNA Breaks, Double-Stranded; Dose-Response Relationship, Radiation; dvouřetězcové zlomy DNA; kaspasy; ionizující záření; Radiation, Ionizing; myoblasty; serum starvation stress; lidé; myoblast; Caspases; proliferace buněk; Cilia; apoptóza; buněčné linie; Cell Line; Cell Proliferation; Cell Differentiation; primary cilium; poškození DNA; DNA Damage; cell line; centrozom; ionizing radiation; Apoptosis